The agrarian reform, between memory and forgetfulness - Hall, Ingrid (2013)
Although the Peruvian Agrarian Reform has been a mayor event for the peasant communities of Peru, especially in the Andes, it is barely evoked. It is the case of the community of Llanchu, located in the region of Cusco y in the Province of Calca, even if it has born thanks to the reform. In this paper we will analyse the way people refers to the agrarian reform. We will show that discourses about the past are socially controlled as any other kind of speech in that society. We will also discuss the way this past is engraved in the society and its territory. The ancient categories former to the reform are then still in use today even if they are expressed in new words. We will finally discuss the fact that the forgetfulness of the reform makes this community appear like a long-date one. The main question raised here is “what is supposed to be a peasant community today in the Peruvian Andes?” Is that so important to show a social unity and a historical continuity? This point is especially crucial today, as those populations entered in a process of ethnicization.